Ethnobotanical Investigation of Crop Weed Diversity and Their Uses in the Treatment of Diabetes and Other Ailments in Sambalpur, Angul and Dhenkanal District of Odisha (India) - Suman Kumar Mekap, Prasana Kumar Panda, Sagar Kumar Mishra, Monalisa Mahapatra, Chinmaya Chidananda Behera (International Journal of Modern Agriculture, 2020)
An ethnobotanical investigation was instigated in three selected forest surrounded village areas namely Bamra, Chhendipada and Kapilash of Sambalpur, Angul and Dhenkanal district respectively in different crop fields of rice in warm rainy season and in mustard, black gram and groundnut in winter season. Some local occupants including both tribal and non-tribal were approached and interviewed to identify, name and show the weeds in these crop fields, which they use for medicinal purposes to cure both animal and human ailments with special reference to diabetes. We identified total 75 weed species present in three villages under study, it was revealed that common people use only 53 species for their curative purposes. Some of the promising ethnomedicinal weeds identified as Alternanthera sessilis, used in dysentery; Amaranthus spinosus, used in abscesses and eczema; Blumea lacera used to hasten the expulsion of placenta of cow after calving; Chenopodium album, used to improve appetite and abdominal pains; Cynodon dactylon used as antihaemorrhagic in dysentery and nasal bleeding; Cyperus rotundus roots are useful in dysentery, vomiting and epilepsy; Eclipta prostrata used as anthelmintic and wound healing; Euphorbia hirta, in ring worm and old wounds; Heliotropium indicum used in joint disorders; Marsilea minuta used in sleeplessness and insect bites, Oxalis corniculata used in the treatment of diabetes and hyperlipidemia, Portulaca pilosa used in weight reduction and diabetes etc.